2019
DOI: 10.1111/tbed.13207
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and zoonotic potential of rotavirus A strains in the southern Andean highlands, Peru

Abstract: Interspecies transmission is an important mechanism of evolution and contributes to rotavirus A (RVA) diversity. In order to evaluate the detection frequency, genetic diversity, epidemiological characteristics and zoonotic potential of RVA strains in faecal specimens from humans and animals cohabiting in the same environment in the department of Cusco, Peru, by molecular analysis, 265 faecal specimens were obtained from alpacas, llamas, sheep and shepherd children, and tested for RVA by RT‐PCR. Genotyping was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…Two lineages showed a close relationship between Uruguayan bovine strains and human strains (from South America and Europe); these human strains were reported to be Artiodactyl-like and a product of interspecies transmission [ 10 , 47 , 50 ], as well as the goat strain of a third lineage [ 45 ], which is in accordance with our results. In the NSP2-5 and VP6 genes, we observed that the Uruguayan bovine strains clustered in some lineages with strains isolated from other host species (human, goat, guanaco, vicuna, roe deer, llama, and sheep), mainly from South America, that were proposed to be originated by interspecies transmission [ 12 , 45 , 47 , 51 ], again in accordance with our results. Another piece of evidence supporting this event was observed in the NSP4; all the RVA strains detected in South America were E12, independent of the host species where they were isolated (horse, cow, guanaco, human, goat), suggesting interspecies transmission and fixation of this genotype in South America [ 44 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Two lineages showed a close relationship between Uruguayan bovine strains and human strains (from South America and Europe); these human strains were reported to be Artiodactyl-like and a product of interspecies transmission [ 10 , 47 , 50 ], as well as the goat strain of a third lineage [ 45 ], which is in accordance with our results. In the NSP2-5 and VP6 genes, we observed that the Uruguayan bovine strains clustered in some lineages with strains isolated from other host species (human, goat, guanaco, vicuna, roe deer, llama, and sheep), mainly from South America, that were proposed to be originated by interspecies transmission [ 12 , 45 , 47 , 51 ], again in accordance with our results. Another piece of evidence supporting this event was observed in the NSP4; all the RVA strains detected in South America were E12, independent of the host species where they were isolated (horse, cow, guanaco, human, goat), suggesting interspecies transmission and fixation of this genotype in South America [ 44 ].…”
Section: Discussionsupporting
confidence: 90%
“…In South America, it is common to raise different livestock species on the same farm in close contact with humans [ 45 ], which increases the possibility of interspecies transmission. Our results support that interspecies transmission is a common event in South America, including the possibility of zoonotic transmission [ 45 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 84%
“…The samples of toucan (Ramphastus sp.) and cockatiel (Nymphicus hollandicus) were grouped in a different clade, but showed high nucleotide homology (99% and 100%, respectively) to strains circulating in llamas [41]. This genotype is considered the most virulent, justifying the diarrheal condition evidenced by the animals grouped in the G3 genotype [40].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is the first report of the circulation of genotype P [2] in Brazil. Recently, Rojas et al [41] reported the unusual genotype P [2] circulating in llamas, alpacas and humans in Peru, thus revealing the zoonotic potential associated with the circulation of genotypes G1 and G3 in these animals. The findings suggest the close interaction of humans and wild animals that can result in the breaking of the barrier between species, resulting in the adaptation of RV to new hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly high frequencies of G and P mixed genotype infections were observed in children 416 sampled in India (three studies showing multiple G types in 11.3 %, 12% and 21% of samples) (Husain, Seth et 417 al. 1996, Jain, Das et al 2001, Khetawat, Dutta et al 2002, Spain (>11.4% of samples) (Sánchez-Fauquier, 418 Montero et al 2006), Kenya (5.9%) (Kiulia, Peenze et al 2006), Africa (12%) (Mwenda, Ntoto et al 2010), and 419 Mexico (5.6% in 2010Mexico (5.6% in , 33.5% in 2012 (Rojas, Dias et al 2019). In another study, whole genome deep sequencing revealed that 15/61 (25%) 423 samples obtained in Kenya contained multiple rotavirus genotypes (Mwanga, Nyaigoti et al 2018).…”
mentioning
confidence: 99%